Critical ethnography methods, ethics, and performance - Madison, D. Soyini
Whilst exploring the ethics of ethnography, this book illustrates the relevance of performance ethnography across disciplinary boundaries, exploring links between theory & method, various theoretical concepts & a number of methodological techniques